The effect of acidulated phosphate fluoride application on dental enamel surfaces hardness - Edhie Arief P; Sri Kunarti (Dental Journal (Majalah Kedokteran Gigi), 2007)
Enamel demineralization by acid is the first step of caries process. It has recently been shown that acidulated phosphate fluoride (APF) can maintain the hardness of enamel surface. The aim of this study was examine the effect of APF application in the hardest of enamel surface. Fifty extracted teeth were cut at their crown, 40 teeth were taken randomly then divided into 4 groups, group 1 as the control, group 2 was treated with APF for 1 minute, group 3 for 4 minutes and group 4 for 7 minutes, then all the samples were washed with demineralized water. To see the effect of APF, all of the samples were soaked in lactic acid demineralization solution with pH 4,5 for 72 hours., the hardness of the surfaces of those samples before and after the treatment was measured by Micro Vickers Hardness Tester. The data were analyzed using One-Way ANOVA and LSD tests. In conclusion, 1.23% APF gel can reduce higher enamel demineralization.